Tissue prolapse-induced acute stent thrombosis: a case report and intravascular imaging-based insight - Zhang, Weifeng; Jia, Shengqi; Wu, Yanmin; Jia, Haiyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute stent thrombosis (AST) is a rare but serious complication occurring within 24 h after percutaneous coronary intervention (PCI), typically caused by insufficient antiplatelet therapy, stent under-expansion, or malapposition. Tissue prolapse (TP) within the stent is less frequently reported as a cause of AST and lacks direct imaging-based evidence.Case summaryWe report a case of a patient with acute ST-segment elevation myocardial infarction (STEMI) who experienced recurrent ST-segment elevation 1 h after primary PCI. Coronary angiography revealed mid-stent occlusion, and intravascular ultrasound (IVUS) identified tissue prolapse with echogenic features consistent with fibrolipidic plaque. The initial stent was appropriately sized and well-deployed, and activated clotting time (ACT) indicated adequate anticoagulation. In the absence of traditional risk factors for AST, the large-volume tissue prolapse was considered the likely cause. Balloon angioplasty failed to resolve the prolapse, so an additional stent was implanted at the site. After this intervention, no further thrombotic events occurred.ConclusionThis case provides clear intravascular imaging evidence that tissue prolapse can induce AST. For cases of early stent thrombosis with angiographic haziness and no signs of dissection or malapposition, clinicians should suspect tissue prolapse. Intravascular imaging facilitates accurate diagnosis and helps guide treatment. Further research is warranted to define high-risk features of tissue prolapse—such as volume, protrusion, and composition—to establish thresholds and interventional criteria that may prevent AST.